Doctoral Student Socialization: Educating Stewards of the Physical Education Profession. Issue 4 (1st October 2016) - Russell, Jared; Gaudreault, Karen Lux; Richards, K. Andrew R.
ABSTRACT: In preparing the future stewards of the physical education profession, the occupational socialization and professional development of physical education doctoral students is important to consider. To date, there has been scant scholarly inquiry into doctoral education in physical education. However, there is an abundance of research related to doctoral training in the higher education literature more generally. Drawing upon this larger body of work, this article expands occupational socialization theory to address the socialization of physical education doctoral students and faculty members. The case is made that effective doctoral training in physical education is essential to securing the future of the profession. Provided is an overview of the existing literature, presentation of an adaptation to occupational socialization theory that explains doctoral physical education socialization, and a discussion of key professional development issues that academic leaders and student support personnel should consider. Implications and recommendations for doctoral physical education leadership and academic programs are provided.